Assessment of the Incidence of Iron Deficiency Anemia among Women - Aslonova I. Zh. (American Journal of Biomedicine and Pharmacy, 2025)
This paper presents the results of a study of the regional causes of the development of iron deficiency anemia (IDA) in women of fertile age based on a prospective study of anemic patients and a retrospective analysis of 1515 medical records. In the course of the studies, it was found that IDA still occupies a leading position in the spectrum of extragenital diseases in women of fertile age. Over the past 20 years, there has been an inconspicuous change in the leading causes of the development of iron deficiency. Together with the former leader, in the form of frequent childbirth, iatrogenic metrorrhagias and dysmenorrhea, as well as alimentary factors and a shortened birth interval, rose to the fore